Pemberdayaan siswa Madarsah Aliyah dalam pemanfaatan sampah menjadi barang bernilaiguna di Desa Mumbulsari - Wakit, Saipul (Jurnal Suluah Komunitas, 2023)
Garbage is an item that is discarded by someone who is considered unusable. Waste problems must be addressed and anticipated by all elements and stakeholders, because if they are not taken seriously, waste can cause various problems in the community. This community service activity was carried out at the Private Islamic Senior High School in Mumbulsari village. Objectively, the main problems faced by partners are 1) Do not understand in the technical details of good and correct waste management, 2) Do not have skills in utilizing waste, 3) There is no product from waste basic materials that has use value and economic value. The solutions carried out are socialization activities to increase understanding of waste management, workshops on the use of waste into useful goods, as well as providing education, awareness and care for the environment (environmental education). The results of this activity increase knowledge, skills and the existence of products produced by partners that can provide benefits, artistic and economic.Keywords: Utilization, Waste, Goods and Useful Value